Polymorbidity and indicators of carbohydrate, lipid and purine metabolism in patients with arterial hypertension - Yu. A. Nikolaev; V. Ya. Polyakov; I. M. Mitrofanov; E. V. Sevostyanova; I. I. Kovrigin (Сибирский научный медицинский журнал, 2021)
Aim of the study was to investigate the peculiarities of the relationship of polymorbid pathology in arterial hypertension with disorders of lipid, purine and carbohydrate metabolism. Material and methods. Patients with arterial hypertension with the presence of polymorbid pathology, who underwent examination and treatment at the clinic of the Federal Research Center for Fundamental and Translational Medicine (Novosibirsk), were examined. A total of 9775 people were examined. The patients were divided into 2 groups: with arterial hypertension in the dyslipidemia absence (n = 561(252 men (44.9 %), 309 women (55.1 %), average age 57.1 ± 0.60 years) and in the dyslipidemia presence (n = 9214 (3879 (42.1 %) men, 5335 (57.9 %) women, average age 57.82 ± 0.12 years). Results and discussion. Hyperglycemia and hyperuricemia were more common in patients with arterial hypertension with dyslipidemia; the indicators were statistically higher: total serum cholesterol, low-density lipoprotein cholesterol, triglycerides, atherogenic index, serum glucose, uric acid compared with patients with arterial hypertension without dyslipidemia. In patients with dyslipidemia, compared with patients without dyslipidemia, arterial hypertension was more often combined with diseases of the endocrine system, nutritional disorders and metabolic disorders, and other diseases of the circulatory system. Conclusion. The data obtained can serve as a theoretical basis for the concept of care for polymorbid patients, based on the impact on the main key pathogenetic mechanisms of diseases, and new approaches to complex treatment, rehabilitation and personalized prevention, taking into account the impact on modifiable risk factors.